2021
DOI: 10.1002/hbm.25423
|View full text |Cite
|
Sign up to set email alerts
|

Human immune deficiency virus‐related structural alterations in the brain are dependent on age

Abstract: Currently, it is still unknown whether human immune deficiency virus (HIV)‐related structural alterations in the brain are dependent on age. With people living with HIV at different ages, we aim to investigate age‐specific structural alterations in HIV patients. Eighty‐three male HIV patients and eighty‐three age‐matched male controls were enrolled, and high‐resolution T1 weighted images were collected and analyzed with four morphological metrics. Then, statistical analyses were respectively conducted to ascer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
(47 reference statements)
2
7
0
Order By: Relevance
“…dMRI has been used to accurately detect the effect of HIV on brain WM abnormalities and determine the relationship between cognitive functions and other factors, such as smoking, age, and drug use. [40,[49][50][51] Our findings not only revealed CPT, FX, and SLF abnormalities in HIV patients, which have been reported in previous DTI studies, [52][53][54][55] but also reported some new findings in FPT, CRF, RST, CBT, CPT and VLPC tracts. Indeed, recent fixel-based analytical approaches have been widely applied for characterizing a specific fiber population within a voxel (i.e., a "fixel").…”
Section: Discussionsupporting
confidence: 88%
“…dMRI has been used to accurately detect the effect of HIV on brain WM abnormalities and determine the relationship between cognitive functions and other factors, such as smoking, age, and drug use. [40,[49][50][51] Our findings not only revealed CPT, FX, and SLF abnormalities in HIV patients, which have been reported in previous DTI studies, [52][53][54][55] but also reported some new findings in FPT, CRF, RST, CBT, CPT and VLPC tracts. Indeed, recent fixel-based analytical approaches have been widely applied for characterizing a specific fiber population within a voxel (i.e., a "fixel").…”
Section: Discussionsupporting
confidence: 88%
“…We identified some similarities with other studies such as atrophy of the precuneus (47). We detected that AD had reduced GMV at the ITG r and ITG l (48), SFG l (49), MSFG r (49), right gyrus rectus or straight gyrus (49) right temporal lobe (50), left putamen (51) and right precuneus. Furthermore, Guo, Chen (52) found decreased GMV in the ventral precuneus and postulated that this region helps to boost the efficiency of conscious processes, allowing individuals to transition between different temporal frames depending on the situation and leading to more balanced time perspectives, which then becomes impaired in AD patients.…”
Section: Discussionmentioning
confidence: 95%
“…The reparametrized module was designed to constrain the similarity of deep semantic features, achieving the most distinguishing features. The morphological metrics were derived from VBM (Jing et al, 2018;Zhao et al, 2021), where GMV, white matter volume, and cerebrospinal fluid volume were computed using CAT-12.…”
Section: Methodsmentioning
confidence: 99%